Corporate site visit and tax avoidance: The effects of monitoring and tax knowledge dissemination - Guo, Yingwen; Li, Jingjing; Lin, Bingxuan (Journal of Corporate Finance, 2023)
This study examines how institutional investors' corporate site visits affect tax avoidance. Using quantile regressions, we find that corporate site visits decrease tax avoidance for firms at high levels of tax avoidance and increase tax avoidance for firms at low levels. The effect of corporate site visits on tax avoidance is stronger for firms subject to a weaker information environment, which suggests that institutional investors acquire additional firm-specific information via corporate site visits and play a more effective monitoring role. We also find that visitors who visited low-tax firms in prior years share tax-planning knowledge with high-tax firms which they visit in the current year. The effect of tax knowledge transfer is more pronounced when the visitors are from incumbent institutional shareholders. This study identifies corporate site visits as a channel via which institutional investors serve as monitors to managers and as facilitators of tax knowledge transfer.